Comparative Genomics of Escherichia coli Sequence Type 219 Clones From the Same Patient: Evolution of the IncI1 blaCMY-Carrying Plasmid in Vivo - Kao, Cheng-Yen; Chen, Jenn-Wei; Liu, Tsung-Lin; Yan, Jing-Jou; Wu, Jiunn-Jong (Frontiers in Microbiology, 2018)
This study investigates the evolution of an Escherichia coli sequence type 219 clone in a patient with recurrent urinary tract infection, comparing isolate EC974 obtained prior to antibiotic treatment and isolate EC1515 recovered after exposure to several β-lactam antibiotics (ceftriaxone, cefixime, and imipenem). EC974 had a smooth colony morphology, while EC1515 had a rough colony morphology on sheep blood agar. RAPD-PCR analysis suggested that both isolates belonged to the same clone. Antimicrobial susceptibility tests showed that EC1515 was more resistant to piperacillin/tazobactam, cefepime, cefpirome, and ertapenem than EC974. Comparative genomic analysis was used to investigate the genetic changes of EC974 and EC1515 within the host, and showed three plasmids with replicons IncI1, P0111, and IncFII in both isolates. P0111-type plasmids pEC974-2 and pEC1515-2, contained the antibiotic resistance genes aadA2, tetA, and drfA12. IncFII-type plasmids pEC974-3 and pEC1515-3 contained the antibiotic resistance genes blaTEM-1, aadA1, aadA22, sul3, and inuF. Interestingly, blaCMY-111 and blaCMY-4 were found in very similar IncI1 plasmids that also contained aadA22 and aac(3)-IId, from isolates EC974 (pEC974-1) and EC1515 (pEC1515-1), respectively. The results showed in vivo amino acid substitutions converting blaCMY-111 to blaCMY-4 (R221W and A238V substitutions). Conjugation experiments showed a high frequency of IncI1 and IncFII plasmid co-transference. Transconjugants and DH5α cells harboring blaCMY-4 or blaCMY-111 showed higher levels of resistance to ampicillin, amoxicillin, cefazolin, cefuroxime, cefotaxime, cefixime, and ceftazidime, but not piperacillin/tazobactam, cefpime, or ertapenem. All known genes (outer membrane proteins and extended-spectrum AmpC β-lactamases) involved in ETP resistance in E. coli were identical between EC974 and EC1515. This is the first study to identify the evolution of an IncI1 plasmid within the host, and to characterize blaCMY-111 in E. coli.